Percuteneous Trans-Mitral Commissurotomy (PTMC); Procedural Success and Immediate Results, an Experience from Tertiary Care Hospital in Northern Division of Bangladesh (University Heart Journal, 2020)
Background: One of the ultimate grave consequences of rheumatic heart disease is mitral stenosis. Percutaneous trans-mitral commissurotomy (PTMC) has been practiced with good results in the world since Inoue introduced it in 1982.Objective: The aim of this study was to audit the procedural success, in- hospital outcome in patients undergoing PTMC in our set up. Study Design: Observational cross sectional study. Place and Duration: The study was conducted in northern division of Bangladesh with the collaboration of department of cardiology, Rangpur Medical College Hospital, Rangpur & Zia Heart Foundation, Dinazpur from February 2018 to November 2019.Materials and Methods: Total Thirty patients who fulfill the inclusion and exclusion criteria for PTMC was enrolled in this study. Among them the procedural success & immediate results were assessed.Results: Among 30 patients , 22(73.33%) were female and 8(26.66%) were male showing a female predominance. The mean age was 28.28±8.4.The procedure was successful in 29(96.66%) patients. In 1(3.3%) patient, we failed due to inability to puncture the septum for unfavourable anatomy. There was no mortality related to the procedure, no systemic embolization but one patient (3.33%) had significant MR(G II ). Pre PTMC mean MVA (cm2) was 0.801± 0.1325 and post PTMC it was 1.545± 0.292 cm2. Mean MVPG pre PTMC was 27.108±5.94 mmHg and post PTMC , 6.61±5.008 mmHg with significant p value 0.0001. Mean LA pressure before procedure was 28.65±8.456 mmHg and post PTMC, 11.27±6.34 and p value was 0.0001. Most of the patients 25(83.3%) before PTMC were in severe pulmonary hypertension and after PTMC most of the patients 21(70%) were in mild pulmonary hypertension.We successfully done 7 special cases like pregnancy, re do cases, H/O CVD etc.Conclusions: We conclude that PTMC is a safe procedure in experienced hand with good success rate and optimal results even in patients with special problems like pregnancy, previous CVA and redo cases.University Heart Journal Vol. 17, No. 1, Jan 2021; 47-54